2018
DOI: 10.1186/s13071-018-2958-6
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity and species diversity of the Ostertagiinae Lopez-Neyra, 1947 in ruminants: a European perspective

Abstract: BackgroundNematodes of the subfamily Ostertagiinae appear to be rather specific to a species or family of hosts, but some are observed in a wide variety of hosts. The nematode Ostertagia leptospicularis draws special attention due to its presence or absence among the same host species in different European countries. Therefore, this paper focuses mainly on the host specificity among nematodes of the subfamily Ostertagiinae. The second aim of this study is to assess the possibility of treating O. leptospiculari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Furthermore, nematodes from the latter strain circulate within particular host species that can be seen in the morphological variations of specimens derived from roe deer, red deer, and fallow deer. It is also consistent with the results of our prior study where roe deer were identified to be a principal host of O. leptospicularis [ 1 ]. The aforementioned circulation may also exist among bovid host species, which requires further analyses, enriched with a wider molecular approach.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, nematodes from the latter strain circulate within particular host species that can be seen in the morphological variations of specimens derived from roe deer, red deer, and fallow deer. It is also consistent with the results of our prior study where roe deer were identified to be a principal host of O. leptospicularis [ 1 ]. The aforementioned circulation may also exist among bovid host species, which requires further analyses, enriched with a wider molecular approach.…”
Section: Discussionsupporting
confidence: 93%
“…The location of the studied sequences in the presented tree at a considerable distance from each other, when isolated from the same or close phylogenetically host species, could be the basis for inferring the randomness of the formation of separate populations. Our previous study [ 1 ] showed that nematodes of the subfamily Ostertagiinae appear to be rather specific to a species or family of hosts. Thus, the presented phylogenetic tree was extended to other Ostertagiinae species and their hosts, and it showed that O. leptospicularis form separate populations specialized in colonizing one type of host.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies are needed to fully assess the changes related to extremely intensive parasitic infections in moose and to determine their impact on the health status of individual moose. It is important to note that the damage caused by endoparasites is often insidious, and the effects may only become apparent in the long term [ 51 ]. Therefore, there is a strong need to monitor parasitic infections in the unique moose population of central Europe.…”
Section: Discussionmentioning
confidence: 99%